The Determinants of Corporate Cash Holding in Indonesia: Manufacturing Company - Muhammad Ilham Prasetyo Sitorus; Ika Pratiwi Simbolon; Andrianantenaina Hajanirina (President University Press, 2020)
This research has the purpose of analyzing the cash flow, capital expenditures, liquid assets, tangible assets, bank debt, firm size, research and development, growth opportunities, leverage, cash flow volatility, managerial ownership toward cash holding. The population in this research are all manufacturing firms listed on the Indonesia Stock Exchange (IDX). The sampling technique uses a purposive sampling method, and 78 observations have obtained from 26 companies for the 2016-2018 period. The method used in this research is quantitative. The results of this study indicate that liquid assets, tangible assets, and leverage have significant impact on cash holdings. In contrast, cash flow, bank debt, capital expenditure, firm size, research and development, growth opportunities, cash flow volatility, and managerial ownership do not have significant impact on cash holding.